2009
DOI: 10.1016/j.ajic.2008.12.002
|View full text |Cite
|
Sign up to set email alerts
|

APIC State-of-the-art Report: The role of the infection preventionist in emergency management

Abstract: Infection preventionists need to become more involved in emergency management at the personal, facility, and community level. This report outlines the infection preventionist's responsibilities related to emergency management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…Although hospital and ED planners often rely on information from their individual facilities, integration of broader surveillance information from the city, state, or national level can provide increased awareness and earlier detection of an impending threat [33], [34], [35], [36]. Previously, hospital and ED planners have used surveillance information to understand disease prevalence for testing and treatment decisions, institute infection control precautions to contain outbreaks, and anticipate ED surge [33], [34], [35], [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although hospital and ED planners often rely on information from their individual facilities, integration of broader surveillance information from the city, state, or national level can provide increased awareness and earlier detection of an impending threat [33], [34], [35], [36]. Previously, hospital and ED planners have used surveillance information to understand disease prevalence for testing and treatment decisions, institute infection control precautions to contain outbreaks, and anticipate ED surge [33], [34], [35], [36].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, hospital and ED planners have used surveillance information to understand disease prevalence for testing and treatment decisions, institute infection control precautions to contain outbreaks, and anticipate ED surge [33], [34], [35], [36]. Particularly for anticipation or detection of ED surge, surveillance has lead to increased ED capacity and staffing, purchase of additional supplies, and reallocation of hospital resources such as staffing and beds [33], [36].…”
Section: Discussionmentioning
confidence: 99%
“…[6] Study has shown that nurses' tendency to respond to hazardous incidents such as biological events may depend on their own personal and domestic safety as well as having the required clinical competencies, and such matters should be taken into account. [2526] There are numerous international reports regarding secondary contamination of hospital staff after incidents involving chemical and biological hazards. Therefore, employees should increase their knowledge about the standard decontamination process, managing the infected waste and contaminated bodies.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, employees should increase their knowledge about the standard decontamination process, managing the infected waste and contaminated bodies. [252658]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation